The research on the west side of the hittite emperial ruins in Sivas-Altinyayla (Kuşakli-Sarissa) [Sivas-Altinyayla'da (Kuşakli-Sari̇sa) bulunan hitit uygarliǧina ait kalintilarinin bati kisminin araştirilmasi] - (:unkn) unknown (My University, 2006)
In recent years, geophysical approaches are being frequently used in modelling and in pre-process before the excavation of archeological ruins. Magnetic approach has been used in the archeological ruins in Sivas- Altinyayla, Turkey. The boundaries of the buried structure is being detected by wavelet methods to the total magnetic anomaly map. © 2006 IEEE.